Endoscopic submucosal dissection for silent gastric Dieulafoy lesions mimicking gastrointestinal stromal tumors: Report of 7 cases—a case report series. Issue 36 (September 2016) - Chen, Xue; Cao, Hailong; Wang, Sinan; Wang, Dan; Xu, Mengque; Piao, Meiyu; Wang, Bangmao
Abstract: Background: Dieulafoy lesion is a rare but serious cause of gastrointestinal hemorrhage. However, some cases can be occasionally found without bleeding during the endoscopic screening, and the management remains unclear. The aim of this article was to report the efficacy and safety of endoscopic submucosal dissection (ESD) for silent gastric Dieulafoy lesions, which presented as protrusion lesions mimicking gastrointestinal stromal tumors (GISTs). Methods: Data from the patients with gastric protrusion lesions who underwent ESD from September 2008 to April 2016 in General Hospital, Tianjin Medical University, China were recorded. Seven cases with pathological diagnosis of Dieulafoy lesion without bleeding were enrolled for further analysis. Results: A total of 7 patients (2 males and 5 females) with mean age of 57.7 ± 4.15 years were pathologically diagnosed as Dieulafoy lesion. Four of the lesions were located in gastric antrum, 2 in the fundus, and 1 in the body of stomach, respectively. The mean sizes of the Dieulafoy lesions under white light endoscopy and endoscopic ultrasonography (EUS) were 1.06 ± 0.28 and 0.84 ± 0.29 cm. The origins of these lesions were submucosa (6/7, 85.7%) and muscularis propria (1/7, 14.3%). Three of them appeared with mixed echo under EUS, 3 with hypoechogenicity, and 1 with hyperechogenicity. En bloc complete resection was achieved in all the lesions by ESD with average time of 76.00 ± 16.86 minutes, and no intraoperative bleeding happened. In addition, all patients were followed up for 1 to 53 months, and no recurrence or long-term complications was observed. Conclusion: Therefore, ESD can be an effective and safe treatment for silent gastric Dieulafoy lesions with clinical presentations of submucosal protrusion lesions mimicking GISTs.